Hepatocellular carcinoma risk assessment using gadoxetic acid‐enhanced hepatocyte phase magnetic resonance imaging. Issue 13 (24th April 2014) - Komatsu, Nobutoshi; Motosugi, Utaroh; Maekawa, Shinya; Shindo, Kuniaki; Sakamoto, Minoru; Sato, Mitsuaki; Tatsumi, Akihisa; Miura, Mika; Amemiya, Fumitake; Nakayama, Yasuhiro; Inoue, Taisuke; Fukasawa, Mitsuharu; et al.
Abstract : Aim: To investigate whether the patients with hypovascular liver nodules determined on the arterial phase and hypointensity on the hepatocyte phase gadoxetic acid‐enhanced magnetic resonance imaging (hypovascular hypointense nodules) are at increased risk of hepatocarcinogenesis, we assessed subsequent typical hepatocellular carcinoma (HCC) development at any sites of the liver with and without such nodules. Methods: One hundred and twenty‐seven patients with chronic hepatitis B or C and without a history of HCC, including 68 with liver cirrhosis, were divided into those with (non‐clean liver group, n  = 18) and without (clean liver group, n  = 109) hypovascular hypointense nodules. All the patients were followed up for 3 years, and HCC development rates and risk factors were analyzed with the Kaplan–Meier method and the Cox proportional hazard model, respectively. Results: A total of 17 patients (10 in the non‐clean liver group and seven in the clean liver group) developed typical HCC. Cumulative 3‐year rates of HCC development were 55.5% in the non‐clean liver group and 6.4% in the clean liver group ( P  < 0.001), and those at the different sites from the initial nodules was also higher in the non‐clean liver group (22.2%) than the clean liver group (6.4%) ( P  = 0.003). Multivariate analysis identified older age ( P  = 0.024), low platelet counts ( P  = 0.017) and a non‐clean liver ( P  < 0.001) as independent risk factors for subsequent HCC development. Conclusion: Patients with hypovascular hypointense liver nodules are at a higher risk for HCC development at any sites of the liver than those without such nodules.